Answers

2015-07-02T00:10:36+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
1) Find the formula...
     x= -(b) +- (the square root of) (b)(squared) -4(a)(c)all over 2(a)
2) Determine the values a, b and c
     x2 -10x = 0
   a = 1 (all variable with no numerical coefficient = 1) b = -10 c = 0( if 'c' or 'b' is not shown to any equation = 0)
3) Substitute the value.
     x = -(-10) +- (the square root of) (-10) squared - 4(1)(0) all over 2(1)
4) Simplify
     x = 10 +- (the square root of) 100 - 0 all over 2
     x = 10 +- 10 all over 2
5) Separate the two combining signs
     x1 = 10 + 10  all over 2
     x1 = 20 \20
     x1 = 1
     x2 = 10 - 10 all over 2
     x2 = 0 \2
     x2 = 0
Then that's it!!

0